A review article on knowledge of tubercular adolescent regarding Anti-tuberculosis therapy (ATT) - Pimpalkar, P. N. (International Journal of Nursing Research, 2023)
Abstract: Worldwide many infections are harmful and pathogenic to animals and humans. Tuberculosis (TB) remains one of the most common and leading deadliest diseases, and is one of the most ancient diseases of humankind and has co-evolved with humans for many thousands of years or perhaps for several million years. A group of closely related bacterial species termed Mycobacterium tuberculosis complex causes tuberculosis. Humans become infected by M. bovis, usually via milk, milk products or meat from an infected animal. In spite of newer modalities for diagnosis and treatment of TB, unfortunately, millions of people are still suffering and dying from this disease. The review focus on various aspects of antituberculosis therapy and related therapeutic potential.